2021
DOI: 10.1111/csp2.505
|View full text |Cite
|
Sign up to set email alerts
|

The future of wildlife conservation funding: What options do U.S. college students support?

Abstract: Insufficient funding is a major impediment to conservation efforts around the world. In the United States, a decline in hunting participation threatens sustainability of the "user-pay, public benefit" model that has supported wildlife

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…Our results were similar to those of Mangun and Shaw (1984), Kellert et al (2017), andLarson et al (2021) in finding general opposition to new user-based tax options for conservation funding, and greater support for industry and state-based tax options. However, our findings differed from Dalrymple et al (2012) who found preferences for user-based taxes for nongame conservation funding.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our results were similar to those of Mangun and Shaw (1984), Kellert et al (2017), andLarson et al (2021) in finding general opposition to new user-based tax options for conservation funding, and greater support for industry and state-based tax options. However, our findings differed from Dalrymple et al (2012) who found preferences for user-based taxes for nongame conservation funding.…”
Section: Discussionsupporting
confidence: 90%
“…The MNRTF is a state-based program that takes revenue from natural resource extraction in the state of Michigan and distributes grants to local and state entities for a wide variety of parks and recreation improvement projects [Michigan Department of Natural Resources (MDNR), 2015]. Industry-based funding models enjoy high levels of public support (e.g., Kellert et al, 2017;Larson et al, 2021) and fish and wildlife interests have capitalized on that support with the introduction of Recovering America's Wildlife Act (RAWA) (Recovering America's Wildlife Act, 2021) in the United States Congress in 2021. Although bipartisan support exists for RAWA, it's future is uncertain at this time.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations